(untitled) (Darya Ganj, New Delhi, 2000)
Contents of material: Online cataloguing systems. Nature and functions of online cataloguing. Multi media resources and online cataloguing. Computers in library services. Cataloguing technologies.
Keywords: Catalogs, library,Library science,Online catalogs